Detection of Elemental Composition of Lubricating Grease Using Laser Induced Breakdown Spectroscopy - Cherry Dhiman; Martha N. Reddy; Kamal Gulati; Mohd. Shahid Khan (Lubricants, 2014)
The elemental composition of lubricating soft grease used in rail engines are studied using laser induced breakdown spectroscopy (LIBS) technique. LIBS spectra of fresh, partially used and fully used grease samples are recorded using time-gated ICCD spectrometer for verification of compositional degradation of the used grease. LIBS spectra of grease samples are analyzed by comparing with emission spectra of elements published by NIST standard database. Many spectral lines of impurity elements like Fe, Cu, Ba, Mg, Mn, Ni, S, Zn, Si, Pb, Ti, Ca and Al present in the grease in ppm or ppb level in trace level concentrations are observed in excess in the used grease mainly due to wear and tear. On the other hand in fresh grease, spectral lines of Ca, Al and Na are observed predominantly.